Role of the presence of transition-metal atoms at the antisites in CrAs, CrSe and VAs zinc-blende compounds - Ozdogan, K.; Galanakis, I.; Sasioglu, E.; Aktas, B. (Elsevier, 2008)
In a recent publication [I. Galanakis, K. Ozdogan, E. Sasioglu, B. Aktas, Phys. Rev. B 74 ( 2006) 140408( R)] we have shown that in the case of CrAs and related transition-metal chalcogenides and pnictides, crystallizing in the zinc-blende structure, the excess of the transition-metal atoms leads to half-metallic ferrimagnetism. The latter property is crucial for spintronic applications with respect to ferromagnets due to the lower stray fields created by these materials. We extend this study to cover the case where the transition-metal atoms sitting at antisites are not identical to the ones in the perfect sites. In Cr-based compounds, the creation of Mn antisites keeps the half-metallic ferrimagnetic character produced also by the Cr antisites. In the case of VAs, Cr and Mn antisites keep the half-metallic character of VAs ( contrary to V antisites) due to the larger exchange splitting exhibited by these atoms. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: electronic structure; half-metals; CrAs; ferrimagnetism